Обробіток деревини на теренах Північної Буковини в ХІІ – першій половині ХІІІ ст. - Возний, Ігор (Археологія і давня історія України, 2020)
I. P. Vozny WOODWORKING IN THE NORTHERN BUKOVYNA DURING 12th — EARLY 13th CENTURIES The article deals with the development of woodworking industry in the medieval settlements of Northern Bukovyna which for a long time remained poor studied. During the Middle Ages this territory was covered with significant forest areas, in which there were 22 local breeds of both industrial and rare trees. Accordingly, the woodworking industry here, as well as throughout the territory of Old Rus, had many branches. Being well acquainted with the technical properties of wood the local masters widely used this knowledge depending on the physical and mechanical properties of the breed. Constructing fortifications they used mainly oak and beech, for residential and commercial buildings they used pine and fir. Hardwood (maple, ash) was spread in manufacturing of dishes, while spoons were made from the yarrow, juniper. The remains of precise or carved wooden dishes were discovered in the settlements of Northern Bukovyna. Beech and oak were used in the craft. Containers were made from lime to store loose materials. Local carpenters were aware of various ways of connecting individual wooden elements to each other in a particular product or construction. When erecting dwellings or household structures in corners, the main method was to connect the locks, and when connected horizontally, direct, overhead, spit joints were widely used. At the archaeological sites of Northern Bukovyna, as the open settlements were almost not explored, considerable woodworking toolkit was discovered. It is represented as forms and fragments of blades, ax, bits, drill bits, knives, nail, etc. Their typology has wide analogies among archeological materials from other territories of the Old Rus state and is fully integrated into the generally accepted typology. Thus, materials that characterize the woodworking industry of Northern Bukovyna completely allow trace the evolution of the woodworking business, which developed in terms of economic development of Old Rus.
Keywords: woodworking; wood; carpenter; bonder; adze.